Is there an association between nurse, clinical teacher and peer feedback for trainee doctors' medical specialty choice? An observational study in Taiwan. Issue 4 (12th April 2018) - Hsu, Chih-Ming; Hsiao, Cheng-Ting; Chang, Li-Chun; Chang, Hung-Yu
Abstract : Objectives: This study explored whether there is an association between medical trainees' future specialty choices and the 360-degree feedback they receive. We hypothesised that the higher the scores that teachers, trainees and/or nurses give to postgraduate year 1s (PGY1s) in any given specialty, the more likely that they will choose that specialty for their residency. Setting: The study was conducted in a large regional teaching hospital in Taiwan. Participants: The participants of this study were n=66 PGY1s who had completed their medical studies domestically or internationally and had received their PGY1 training in a single teaching hospital in southern Taiwan. Data from 990 assessments were included. Primary and secondary outcome measures: Logistic regression analyses for teachers', nursing staff and peers' authentic assessments of trainees were undertaken for (1) desired specialty, (2) applied specialty, (3) enrolled specialty, (4) consistency between desired and applied specialties, (5) consistency between applied and enrolled specialties and (6) consistency between desired and enrolled specialties. Alpha was set at p<0.05. Results: Nursing staff scores were significantly associated with all six dependent variables. Furthermore, teachers' scores were significantly associated with trainees' desired specialty and the consistency between desired and enrolled specialty. Peers' scores were not significantly associated with any dependent variable. Conclusions: Trainees' specialty choices are associated with scores given by nursing staff and clinical teachers. We suggest that qualitative research methods should further explore this association to ascertain whether PGY1s are consciously influenced by these scores and if so, in what way.